Sustainable use and the laws regulating trade in threatened species in South Africa: lessons from the USA - Frantz, Theressa Rosetta (Institute of Marine and Environmental Law, 2018)
This study focuses on sustainable use of threatened or endangered species in the international trade context. Escalating levels of illegal trade in threatened species are of major concern globally and undermines regulatory frameworks that seek to ensure the sustainable use of species for present and future generations. This study investigates the extent to which South African legislation provides for sustainable use and trade in species and how legislation could be strengthened. The study is theoretically underpinned by the concept of sustainable use and its passage through time in 'soft' law and consequent adoption by international law and Conventions, including those to which South Africa is a party. The latter includes the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and the Convention on Biological Diversity (CBD). While commitments to CITES and the CBD are reflected in South Africa's domestic legislation, sustainable use remains an ambitious ideal. A comparative analysis of legislation, relevant case law and literature of the United States of America with that of South Africa, revealed that while the National Environmental Management Biodiversity Act is more contemporary and its Norms and Standards allow for responsive mechanisms to emergency situations, strengthening in key areas would further enhance sustainable use. Recommendations for strengthening the management dimension of South African law include adhering to statutory time-frames, considering a collaborative approach in the public participation process, and improving the Biodiversity Management Plans for species by increasing the emphasis on species recovery in the wild. This requires long term commitment and specific financial resources, while also developing clear criteria for measuring improvement in the threat status of species over time. The challenge for South Africa remains effective enforcement and legislative compliance in ensuring that sustainable use of species is not undermined. South Africa's penalty provisions are stringent, but consistency in application by the judiciary is recommended. Building on the strength of the penalty provisions, it is further recommended that South Africa adopts provisions along the lines of the US Lacey Act for extraterritorial enforcement of foreign law for sustainable use and trade in threatened or endangered species.